Far Eastern federal district: Economic analysis and development problems - Jevgenijs Leontjevs; Inna Dovladbekova (European Regional Science Association (ERSA), 2014)
The main aim of this paper is to define weak spots in the Far Eastern federal district's development in comparison with other federal districts in the Russian Federation based on a statistical and economic analysis, and shape general conclusions on possible improvement of the economic development of the region. Socio-economic disparities between regions are an important issue in many countries. Both state legislation's and governmental institutions' goal is to reduce or eliminate imbalance between regions by implementing regional development plans, creating funds and policies in order to ensure security, stability and prosperity. Regional economic growth and development encompasses multiple disciplines, including geography and planning, regional science, entrepreneurship, technology policy and economics. Bearing different regional development terms put forward by scientists and international organisations it can be pointed out that regional development policy has evolved over the last 50 years from simpler massive investment into infrastructure development to an understanding of region's unique features in order to uncover full potential of the region's competitive advantages by certain plans and policies. Understanding the region's socio-economic, geographical and cultural features is key for elicitation of regional competitive advantages and development policy proposition. Moreover, policy effectiveness assessment backed by a detailed analysis is crucial for new regional development policy proposition. It must be taken into account that despite significant investment projects, aid for growth and regional development some of the largest federal districts by area, in Russia, still fall behind other homeland regions in manufacturing, mining and quarrying, electricity, gas and water: the economic sectors that comprise a powerhouse of the national economy. The underdevelopment some of the largest federal districts of the Russian Federation, regional administrative management inefficiencies and failure to use development funds and programs to their full potential present severe development obstacles and socio economic threats in the future. Policy makers must assess the effectiveness of federal investments, financial aid, foreign investments and overall investment climate and identify major areas of improvement. Moreover, policy makers should work towards improvement of the existing regional strategy or develop a new regional development initiative that includes possible solutions for problematic issues. A new economic development initiative that provides funding for large scale manufacturing deployment projects that encourage economic growth and substitute imported machinery, equipment and vehicles in Far Eastern federal district must be development and implemented.
Keywords: O11; O20; 330; regional development; statistical analysis